Epithelial dysplasia in pterygium postoperative granuloma. (October 2018) - Wang, Guoliang; Dong, Nuo; Wang, Yanzi; Li, Jing; Dong, Fei; Jeyalatha, Vimalin; Wu, Jingwen; Shen, Mei; Yang, Qichen; Chen, Pei; Xue, Yuhua; Liu, Zuguo; et al.
Abstract: Pterygium postoperative granuloma (PPG) is one of the common complications of pterygium surgery. In order to provide the structural features of PPG, and to further explore its pathogenetic mechanism, we analyzed clinical and pathological characteristics of 12 PPG cases. New blood vessels were observed under a slit lamp in PPG and peripheral conjunctival tissues. In vivo confocal imaging showed that there was extensive neovascularization in the stroma, accompanied by infiltration of dendritic cells and inflammatory cells. Dense fibrous structures were observed in some PPG tissues. H&E staining results confirmed neovascularization and inflammatory cells in PPG tissues. In addition, H&E staining exhibited epithelioid tissue covering some PPG tissues. The immunofluorescence results demonstrated that the PPG epithelium was negative for K19, K10 and Muc5AC. Compared with the normal conjunctiva and pterygium, the expression of collagen IV in PPG basement membrane decreased, the expression of pan-cytokeratin (PCK), claudin 4 and E-cadherin in PPG epithelium was significantly lower, while the expression of vimentin, α-SMA and Snail was significantly increased. Therefore, our results suggest that the expression of epithelial keratin markers and goblet cell specific mucin marker is downregulated in the PPG tissues, and it likely is associated with the occurrence of EMT in granulomatous tissues. Highlights: Pterygium postoperative granuloma (PPG）is one of the common complications of pterygium surgery. Broken basement membranes are present in the PPG tissue. PPG epithelial tissue differentiated into an abnormal phenotype which occurs as consequence of the EMT phenomenon.